Relationship Between Gastrointestinal Transit, Medsger Gastrointestinal Severity, and University of California–Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract 2.0 Symptoms in Patients With Systemic Sclerosis. Issue 3 (25th January 2022) - McMahan, Zsuzsanna H.; Tucker, Ana E.; Perin, Jamie; Volkmann, Elizabeth R.; Kulkarni, Subhash; Ziessman, Harvey A.; Pasricha, Pankaj J.; Wigley, Fredrick M.
Abstract : Objective: Systemic sclerosis (SSc)–associated gastrointestinal (GI) complications are attributed to a variety of factors, including diet, microbiota dysbiosis, or GI transit abnormalities. Our objective was to examine the contribution of abnormal GI transit to SSc Medsger GI severity scores and/or University of California Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract (UCLA GIT) 2.0 symptoms. Methods: Patients with SSc and GI symptoms (n = 71) and healthy controls (n = 18) underwent whole gut transit (WGT) scintigraphy to assess transit from the esophagus to the colon. The presence of delayed transit and percent emptying in each GI region were measured. We compared the WGT measurements between categories of the Medsger GI severity score (0–4) and across UCLA GIT 2.0 domains and total score (0–3). Results: A total of 88% of patients had >1 abnormal region of the gut on WGT scintigraphy. All patients requiring total parenteral nutrition had delayed small bowel transit, compared to only approximately 11% of patients in other Medsger GI severity groups ( P ≤ 0.01). Severe colonic transit delays were more likely in patients with Medsger GI scores of 3 (pseudo‐obstruction and/or malabsorption) compared to other Medsger GI groups ( P = 0.02). Seventy‐percent of these patients had ≤30% colonic emptying at 72 hours. Modest associations were noted between gastroesophageal reflux disease symptoms and delayed esophageal (r = –0.31, P = 0.05) and gastric emptying (r = –0.32, P = 0.05). Conclusion: These data are important in providing evidence that SSc bowel disease affects transit of GI content and that delay in transit accounts in part for both bowel symptoms and Medsger GI severity. Prospective studies examining the benefit of early therapeutic intervention targeting GI transit abnormalities in patients at high risk for severe GI complications are needed.